The Impact of Sexual Abuse Experience on the Life Scenarios Manifestations in Middle-Aged Women - Shapoval, Yana (Visnyk of V.N. Karazin Kharkiv National University. Series Psychology, 2025)
The article presents the results of a comprehensive study of the psychological specifics of the impact of sexual violence experiences on the formation and manifestation of life scripts in middle-aged women. The relevance of the research is determined by the growing socio-psychological challenges associated with overcoming the consequences of traumatic events that lead to profound changes in the cognitive, emotional, motivational-value, and behavioral spheres of personality. A life script is conceptualized as an integrated system of meanings, attitudes, and behavioral strategies that determine adaptation, self-realization, and the construction of interpersonal relationships in middle adulthood. The aim of the study was to identify the structural characteristics and correlation relationships between the components of life scripts and the experience of sexual violence, with a particular focus on the possibilities of post-traumatic reconstruction. The methodological framework was based on typological, parametric, and nomothetic approaches implemented within an empirical research design. The study was conducted on a sample of 60 middle-aged women who had survived sexual violence. A set of psychodiagnostic instruments was applied to assess cognitive schemas of post-traumatic experience, emotional reactivity, value-motivational orientations, and behavioral coping strategies. Statistical data processing was carried out using Kendall’s correlation coefficient, which made it possible to identify stable associative links between the indicators. The findings confirmed the presence of a close integration of negative cognitive-affective constructs (self-blame, destructive beliefs about the self and the world, denial of traumatic experience) and maladaptive behavioral patterns. At the same time, pronounced manifestations of post-traumatic growth were revealed, representing positive transformations of the meaning system, increased appreciation of life, expansion of life opportunities, and strengthening of internal resilience. Correlation analysis demonstrated that the restoration of trust in others and the formation of new existential meanings act as key factors in the reconstruction of a traumatic life script. The conclusions substantiate that the experience of sexual violence, although it determines stable maladaptive patterns, simultaneously creates the potential for profound change and development. The proposed empirical model can serve as a basis for the development of crisis-oriented psychological support programs aimed at integrating traumatic experiences and fostering resource-oriented life strategies.